Phyllanthus emblica Prevents Adipogenesis by Regulating Histone Acetylation - Seon Kyeong Park; Yu Geon Lee; Jae-In Lee; Min-Sun Kim; Jae-Ho Park; Jin-Taek Hwang; Min-Yu Chung (Foods)
Phyllanthus emblica is widely used in Ayurvedic preparations against multiple disorders and contains various bioactive components. This study aimed to determine the preventive effect of P. emblica on obesity by evaluating the inhibition of adipogenesis and the related regulatory epigenetic mechanisms during 3T3-L1 differentiation. The ethyl acetate fraction of P. emblica (EFPE) effectively inhibited lipid accumulation and triglyceride (TG) production in 3T3-L1 adipocytes. It also inhibited histone acetyltransferase (HAT) activity and regulated Pcaf-specific H3K9 acetylation and the expression of adipogenesis-related genes during adipocyte differentiation. Phenolic compounds were the main components of EFPE, of which gallic acid (GA) exhibited the strongest inhibitory effect on lipid accumulation and TG production. Notably, GA effectively regulated adipogenesis-mediated gene expression through H3K9 acetylation. These findings, along with the experiment results, suggest that EFPE containing GA is a potent agent for preventing obesity by regulating H3K9 acetylation.